Case Presentation of a 45 Years Old Woman with Hypoglycemia and Bleeding: A case with hypoglycemia and bleeding - Namazi, Soha; Rozitalab, Gholamreza (Iranian Journal of Pharmaceutical Sciences, 2005)
Apatient was admitted to the hospital because of epistaxis, ecchymoses and gum bleeding with INR of 5.5. This patient had a known case of diabetes mellitus type II, 5 years ago. The last dose of glibenclamide for managing signs and symptoms of diabetes mellitus was 20 mg/day. Her medical history also showed that last month she was diagnosed with atrial fibrillation with normal left ventricular ejection fraction (LVEF> 45%) and was placed on warfarin (5 mg) and propranolol (80 mg) daily, which resulted in resolution of atrial fibrilation, a pulse rate of 80 bps and INR of 3 (target INR=2-3). An objective causality assessment indicated the increased effect of warfarin and as a result bleeding could best be explained by drug-drug interaction because there are no other factors such as pathological evidences (e.g. thyroid disease, hepatic disorders) to prove it otherwise. This case is the third report of drug interaction between warfarin and glibenclamide, therefore, this is an interesting and educational case. In view of our experience in the present case, it should be stressed that close monitoring of coagulation capacity is necessary in co-administration of warfarin and other drugs which can affect pharmacokinetic and pharmacodynamic of warfarin.